2002
DOI: 10.1074/jbc.m203247200
|View full text |Cite
|
Sign up to set email alerts
|

Proteinases of the Bone Morphogenetic Protein-1 Family Convert Procollagen VII to Mature Anchoring Fibril Collagen

Abstract: Collagen VII is the major structural component of the anchoring fibrils at the dermal-epidermal junction in the skin. It is secreted by keratinocytes as a precursor, procollagen VII, and processed into mature collagen during polymerization of the anchoring fibrils. We show that bone morphogenetic protein-1 (BMP-1), which exhibits procollagen C-proteinase activity, cleaves the Cterminal propeptide from human procollagen VII. The cleavage occurs at the BMP-1 consensus cleavage site SYAA2DTAG within the NC-2 doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 59 publications
6
93
0
Order By: Relevance
“…8 BMP-1 is a kind of metalloproteinase with conserved domains, and can convert a variety of precursor proteins into mature or active forms that are involved in extracellular matrix formation. 12,13,27,28 It is BMP-1 that converts procollagen types I-III and VII into their mature forms and mediates C-terminal processing of procollagen V homotrimer. 13,27,28 We noted an increased expression of BMP-1 in carcinoma tissues with psammoma bodies or with stromal calcification, which confirms the hypothesized role of BMP-1 in calcification and reveals a possible new role for BMP-1 in the formation of psammoma bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 BMP-1 is a kind of metalloproteinase with conserved domains, and can convert a variety of precursor proteins into mature or active forms that are involved in extracellular matrix formation. 12,13,27,28 It is BMP-1 that converts procollagen types I-III and VII into their mature forms and mediates C-terminal processing of procollagen V homotrimer. 13,27,28 We noted an increased expression of BMP-1 in carcinoma tissues with psammoma bodies or with stromal calcification, which confirms the hypothesized role of BMP-1 in calcification and reveals a possible new role for BMP-1 in the formation of psammoma bodies.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,27,28 It is BMP-1 that converts procollagen types I-III and VII into their mature forms and mediates C-terminal processing of procollagen V homotrimer. 13,27,28 We noted an increased expression of BMP-1 in carcinoma tissues with psammoma bodies or with stromal calcification, which confirms the hypothesized role of BMP-1 in calcification and reveals a possible new role for BMP-1 in the formation of psammoma bodies. We examined the frequency of PBS in 229 cases of papillary thyroid carcinoma and investigated its clinical significance and survival impact.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4). In vitro cleavage assays have confirmed that BMP1, mTLL1 and mTLL2 are capable of cleaving the NC2 domain (Rattenholl et al, 2002), however type VII collagen appears to be fully processed in the skin of mouse embryos null for the Bmp1 gene, which encodes both BMP1 and mTLD (Rattenholl et al, 2002). Thus, mTLL1 and mTLL2 may fully compensate for loss of Bmp1 in these mice, for removal of the procollagen VII NC2 domain.…”
Section: Non-fibrillar Collagensmentioning
confidence: 92%
“…BMP-1, mammalian tolloid, and two highly homologous relatives tolloid-like 1 and 2 constitute the tolloid clade of astacin-like metalloproteinases that have important functions in development and extracellular matrix formation (2). BMP-1 cleaves fibrillar procollagen type I, II, III (3,4), and V (5-7), as well as type VII procollagen (8), prolysyl oxidase (9), probiglycan (10), and the ␥2 chain of prolaminin 5 (11). BMP-1 also cleaves chordin (2) therefore affecting dorsal-ventral patterning in vertebrates (12).…”
mentioning
confidence: 99%